Inspanningsverbintenis dan Resultaatsverbintenis dalam Transaksi Terapeutik Kaitannya dengan UU No. 8 Tahun 1999 tentang Perlindungan Konsumen - sarsintorini putra (Fakultas Hukum Universitas Islam Indonesia, 2001)
The patient comes to the doctor asking to be cure and the doctor agrees with it. it is the of terapeutic transaction, in inspanning sverbintenis, the doctor maximally tries to cure the patient, buthe can not promise a certain recovery. In the resultaatsverbintenis, the agreementis based on the working resuit, for exampie a dentist who makes an artificial teeth, mustfixed to the transaction made with hispatient. In the resultaatsverbintenis can be impiemented in the rule of the customer protection (UU Perlindungan Konsumen, yet in theinspannings verbintenis has become controversy. It is caused for the inspanningsverbintenis and the resultaatsverbintenis, its authority and the responsibility of the doctors are deferent. Therefore, it needs to be understoodin competence, the authority and the responsibility from the medicolegal aspect.